Elite coaches` use and engagement with performance analysis within Olympic and Paralympic sport - Nicholls, S. B.; James, N.; Bryant, E.; Wells, J. (International Journal of Performance Analysis in Sport, 2018)
The use and implementation of performance analysis and feedback by 18 elite Olympic/Paralympic coaches (coaching experience 16.1 ± 7.4; experience using performance analysis 8.3 ± 4.8 years) was explored via an online questionnaire (mean time to complete = 29 min). Likert scales were used to facilitate cross-sport comparison. Comment boxes were included to enable providing additional information if deemed necessary. Training goals, athlete discussion and coaching philosophy were the most prominent features influencing analysis direction. Time available had the greatest impact upon feedback provision. The main analysis techniques used were video, performance reports and trend analysis. Coaches with greater experience delivered significantly more feedback sessions within 1 h of performance. Feedback sessions were < 20 min in duration and delivered in a balanced (experienced) or mostly positive (inexperienced) approach. Feedback was delivered consistently according to a preferred schedule, face-to-face and within an individual format. Sessions were usually coach led; however, considerable value in a combined or analyst-led approach was demonstrated. The findings have begun to illustrate practice within elite sport from the perspective of a key user of performance analysis, that is, the coach, and have clear implications for practitioners by identifying the key areas coaches` value from performance analysis.